Preservation of Viability and Biological Properties of S. aureus and P. aeruginosa after 3 Years’ Storage under –196°C - Vysekantsev, I. P.; Koschij, S. V.; Kudokotseva, E. V.; Shapovalova, O. V.; Belokon, O. N. (Problems of Cryobiology and Cryomedicine, 2006)
The storage of S. aureus and P. aeruginosa bacteria under liquid nitrogen temperature during 3 years provided the preservation for viable cells and biological properties, used for taxonomy and identification of mentioned bacteria. The death of a part of cells is possible at the stage of cooling. Meat-peptone broth (MPB) with sucrose and DMSO additives was used as the preservation medium.